1989
DOI: 10.1063/1.457201
|View full text |Cite
|
Sign up to set email alerts
|

Rotational polarization produced by molecule/LiF (001) collisions in a Knudsen particle flow between 78 and 695 K

Abstract: Molecular angular momentum polarization produced in molecule–surface interaction is investigated by studying the magnetic field effect on a Knudsen flow at temperatures between 78 and 695 K. The effects for H2, D2, HD, N2, and CH4 scattered from LiF (001) are found to be 2–3 orders of magnitude larger than previously observed for other surfaces. This is attributed to the large corrugation of the LiF crystal face, since the polarization type involved depends entirely on the existence of in-plane forces. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…8 In the Knudsen flow experiments, large rotational polarizations were found for the H 2 ϩLiF͑001͒ system, which were attributed in large part to reorientational collisions, in which only the magnetic rotational quantum number m j changes. 6,7 This attribution is in contrast with early theoretical work, which suggested that collisions of H 2 with the surface would be mostly m j conserving. [9][10][11][12][13] In fact, most scattering calculations [11][12][13][14][15][16] performed on this system made use of the potential form introduced by Wolken, 11-13 which contains no dependence on the H 2 azimuthal angle of orientation ͑thereby forbidding ⌬m j transitions͒.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…8 In the Knudsen flow experiments, large rotational polarizations were found for the H 2 ϩLiF͑001͒ system, which were attributed in large part to reorientational collisions, in which only the magnetic rotational quantum number m j changes. 6,7 This attribution is in contrast with early theoretical work, which suggested that collisions of H 2 with the surface would be mostly m j conserving. [9][10][11][12][13] In fact, most scattering calculations [11][12][13][14][15][16] performed on this system made use of the potential form introduced by Wolken, 11-13 which contains no dependence on the H 2 azimuthal angle of orientation ͑thereby forbidding ⌬m j transitions͒.…”
Section: Introductionmentioning
confidence: 71%
“…Detailed results on rotationally and diffractionally inelastic scattering were obtained in experiments performed in the midseventies by Boato et al 4,5 Closely related but more recent results are the rotational polarizations measured in Knudsen flows of H 2 between LiF͑001͒ plates. 6,7 These rotational polarizations can be calculated from S-matrix elements for rotationally and diffractionally inelastic scattering. 8 In the Knudsen flow experiments, large rotational polarizations were found for the H 2 ϩLiF͑001͒ system, which were attributed in large part to reorientational collisions, in which only the magnetic rotational quantum number m j changes.…”
Section: Introductionmentioning
confidence: 99%
“…Then, H 2 was extensively used in scattering experiments on metal 6,7 and dielectrics, 8,9 as a probe of the surface state. This emphasis stimulated theoretical studies related to the determination of accurate potential expressions for the H 2 -surface system and to the adequate description of the molecule dynamics based on quantum mechanics principles.…”
Section: Introductionmentioning
confidence: 99%
“…22,25,26 In this field, the rotational polarization of the moleculesurface scattering is one of the current topics; a phenomenon for which the ⌬m j transitions are essential. 9,17,23,24,27,28 It is thus necessary to perform a five dimensional calculation, taking the azimuthal angle dependence into account. For such calculations, a numerically exact method will meet computational difficulties, in particular when the scattering of a heavy diatom at energies above thermal is considered.…”
Section: Introductionmentioning
confidence: 99%